My life is murder. Series 3 [videorecording (DVD)] - Bell-Booth, Caroline; Smith, Mike (Television director); Lautour, David de; McNaughton, Kiel; Hurst, Michael, 1973-; Hawkshaw, Chris; Lawless, Lucy, 1968-; Vagulans, Ebony; Jobe, Rawiri; Naufahu, Joe; Henderson, Martin, 1974- (Acorn, 2023)
In this new season, while detective Alexa Crowe wrangles her family and friends in her beautiful hometown of Auckland, the show will always focus on compelling episodic mysteries told with humor and heart. And this new series will feature ten new cases that pit Alexa against fascinating, powerful, and surprising suspects everyone from eccentric billionaires to grieving florists, and from tango dancers to fiery fashionistas. The only thing they have in common is that none of them are expecting Alexa's unique brand of crime-solving. But they'll quickly learn that you underestimate Alexa Crowe at your own risk.